Safety and Availability of Basic Process Control Using Foundation Fieldbus with Control in the Field An Experimental Analysis - Thaksin Sangsuwan; Teerawat Thepmanee; Amphawan Julsereewong (My University, 2017)
Detailed knowledge of how to balance between safety and availability for instruments is essential to successful design and implementation in fieldbus-based process control systems.The configuration correctness is crucial to actually obtain the benefits of digital fieldbus technology used.In actuality, a number of device parameters must be set to provide the required functionalities.This paper focuses on improving safety and availability for the proportional-integral-derivative (PID) and cascade control strategies using Foundation Fieldbus (FF) with control in the field.The aim of this paper is to analyze the logical behaviors of PID and cascade loops in two conflicting purposes for studying how different configuration options affect the interlocks between function blocks located in instruments as well as the initialization and fail-safe mechanisms in response to invalid measurements.For safety purpose, the interested control loops are configured to bring the process to a safe state in the presence of a fault.For availability purpose, the interested control loops are configured to keep the process running in the event of a failure.A water tank process is utilized as a case study for control loop implementations.Interactions between the status propagation and mode shedding for demonstrating the studied control loop behaviors are examined experimentally in Petri net models.In addition, the function block options for bumpless transfer and setpoint tracking are also described.The proved configuration method for proper operations in balancing the interests of safety and availability is proposed.
Keywords: Set point; Flexible and Reconfigurable Manufacturing Systems